Exploring the Causes of Child Custody Disputes (Hadhanah) from an Islamic Perspective - Mohammad Hendra; Nurul Hakim (The Indonesian Journal of Islamic Law and Civil Law, 2026)
Child custody (hadhanah) constitutes a fundamental aspect of Islamic law, designed to safeguard the welfare, education, and protection of children following divorce. The principle of justice in Islam emphasizes that the rights of the child must take precedence over parental interests, with due consideration given to compassion, capability, and the suitability of the custodian. This study aims to analyze the concept of child custody from an Islamic perspective, identify the underlying causes of custody disputes, and examine their legal implications within the framework of Indonesia’s religious courts. The research employs a normative approach by reviewing primary sources of Islamic law (fiqh madhhab). The findings indicate that custody disputes arise not only from divergent interpretations of legal provisions but also from practical challenges. These include: (1) the absence of parental affection, which often triggers disputes; (2) financial capacity in relation to child support; (3) the influence of the living environment on parental conflict; and (4) parental customs or traditions that shape approaches to child-rearing.